Pengaruh Promosi Terhadap Jumlah Pendaftar Calon Mahasiswa Baru Pada Akademi Pariwisata Nusantara Tangerang - Wiwid Widiawati; Rizki Nurul Ilmi; Adam samsudin Noor (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2021)
The purpose of this study was to determine the effect of promotion on the number of new student registrations at the Tangerang Nusantara Tourism Academy. This type of research is quantitative research. The population used is all prospective students who register in T.A 2021/2022 as many as 140 students of the Tangerang Nusantara Tourism Academy. the sample was selected as many as 80 respondents. determined by using a random sampling technique. The data collection technique used is the distribution of questionnaires in the form of a questionnaire through the google form application. By using simple linear regression analysis. Data analysis used descriptive statistics, namely by looking for correlation coefficients and simple linear regression using t test. This research was carried out on June 1 - August 31, 2022. Based on statistical results using the SPSS 22.00 application, the results showed "there was a significant effect of promotion on the number of prospective student registrations at the Tangerang Nusantara Tourism Academy" with a promotion percentage rate of 33.98% in increase the number of student registrations.